The Influence of Workload Towards Burnout Among Generation Z Employees in Indonesia: The Mediation Role of Work Stress - Nidya Dudija; Rindu Annisa Putri (Universitas Hayam Wuruk Perbanas, 2025)
This study examines the relationship between workload and burnout, with work stress acting as a mediating variable among Generation Z employees in Indonesia. The research employs a non-probability sampling method, utilizing the Hair for-mula to determine the sample size. Data were collected through a questionnaire, resulting in a sample of 210 Generation Z employees in Indonesia. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that workload has a significant and positive effect on burnout. Additionally, workload significantly and positively impacts work stress, which, in turn, significantly and positively influences burnout. Furthermore, the results demonstrate that work stress mediates the relationship between workload and burnout among Generation Z employees in Indonesia. These findings offer valuable insights for companies in Indonesia, highlighting the importance of man-aging workloads in alignment with employees’ capacities to reduce stress levels and prevent burnout. This is particularly critical for Generation Z employees, who may be more vulnerable to stress in the workplace.